The effect of initiating combined antiretroviral therapy on endothelial cell activation and coagulation markers in South African HIV-infected individuals - Jong, Eefje; Louw, Susan; van Gorp, Eric C. M.; Meijers, Joost C. M.; Cate, Hugo ten; Jacobson, Barry F. (Thrombosis and Haemostasis, 2010)
An increased incidence of venous thromboembolism (VTE) is observed in human immunodeficiency virus (HIV)-infected patients. Only a limited number of studies described the effect of combined antiretroviral therapy (cART) on coagulation markers. In a prospective cohort study in cART-naive South African HIV-infected individuals the effect of initiating cART on markers of endothelial cell activation, coagulation and natural anticoagulation was studied. These markers were compared to the reference ranges for an HIV-uninfected control population recruited from hospital staff. A venous ultrasound of both legs was performed to detect asymptomatic deep venous thrombosis (DVT). A total number of 123 HIV-infected participants were included. The patients were predominantly black and severely immuno-compromised. The CD4 cell count increased and the HIV viral load decreased significantly after the initiation of cART (p<0.001). The median follow-up period was 7.2 (± 1.6) months. Laboratory testing before and after initiation of cART was completed by 86 patients. Before initiating cART significantly elevated von Willebrand factor and D-dimer levels, increased activated protein C sensitivity ratio (APCsr) and decreased total and free protein S and protein C levels were observed compared to HIV-negative controls. At follow-up all markers, except APCsr, improved towards the normal range for controls without showing complete normalisation. In a subgroup of 57 patients no asymptomatic DVT was found. Compared to the controls, abnormal levels of coagulation markers were observed in HIV-infected individuals before and after the initiation of cART. Most markers improved after starting cART, but remained significantly different from the controls, indicating a persistent disturbed haemostatic balance.
Keywords: Coagulation factors; viral infection; venous thrombosis; clinical studies